NEW PLANETARY NEBULAE II - PEIMBERT, M; COSTERO, R (UNAM, Observatorio Astronómico Nacional, CD MEXICO, DF, MEX, 1965)
We present coordinates and identification charts of 14 new planetary nebulae. The data were obtained on objective prism plates, at the Tonantzintla Schmidt camera.
BOL OBS TONAN TACUB
Keywords: NEW, PLANETARY, NEBULAE II; ASTRONOMIA Y ASTROFISICA; PLANETOLOGIA; PLANETAS